Konstruksi Model Pembelajaran Berbasis Partisipatif Pada Mata Pelajaran Pendidikan Agama Islam Di SMAN 1 Parepare - Rustan Efendy; Abdul Rahim Karim; An'nisa Miranti Amri; Hasrina Rahman (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2023)
This study aims to reveal the participatory-based Islamic religious education learning system at SMA Negeri 1 Parepare. A qualitative approach with a case study research method was used to answer the research problem. Data collection techniques used participant observation, structured interviews, and documentation review. Data analysis techniques used the Miles and Huberman interactive model, namely data reduction, data presentation, and verification/ conclusion drawing. While testing the validity of the data is done through credibility (trustworthiness), dependability (dependability), confirmability (certainty), and transferability (transferability). The results of this study indicate that in the context of learning Islamic religious education at SMA Negeri 1 Parepare has been based on participatory, marked by the activeness of students by using the student centered approach paradigm which is the basis of participatory learning. In its implementation, participatory learning provides space for students to actively participate in learning by using a scientific approach using the 5-M principle of questioning, trying, reasoning, associating, and creating.